Characterizing semigroups with commutative superextensions - Banakh, T.; Gavrylkiv, V. (Algebra and Discrete Mathematics, 2014)
We characterize semigroups X whose semigroups of filters φ(X), maximal linked systems λ(X), linked upfamilies N₂(X), and upfamilies υ(X) are commutative.